Influence of Preheating Temperature on Changes in Properties in the HAZ during Multipass MIG Welding of Alloy AW 6061 and Possibilities of Their Restoration - Iva Novakova; Jaromir Moravec; Jan Novak; Pavel Solfronk (Metals, 2021)
Fusion welding of heat-treatable aluminum alloys is generally accompanied by a significant decrease in mechanical properties in the HAZ caused by the dissolution of the hardening phase. The intensity of this decrease in mechanical properties can be reduced by limiting the heat input value. However, this approach is in direct conflict with the principles for welding aluminum and its alloys. Due to the very high thermal conductivity of aluminum alloys, it is necessary to use preheating for thicknesses larger than 5 mm to eliminate non-penetration and cold joints. This paper aims to show the influence of multiple temperature cycles, performed at different preheating temperatures, on changes in the microstructure and mechanical properties. At the same time, the extent to which the original properties of the material can be restored by natural and artificial aging at 160, 175 and 190 °C is also investigated.